Pravda o Černobyle svidetelʹstva živych i mërtvych - Gubarev, Vladimir Stepanovič 1938-2022 (Komsomolʹskaja pravda, 2019)
A collection of eyewitness accounts and interviews with scientists, emergency workers, and others involved in containing the deadly fallout from the Chernobyl nuclear plant explosion